Screening of polypharmacy prescriptions in hypertensive patients at Royal Prima Hospital - Nasution, Nanda Rahma Dewi; Budi, Andre; Lubis, Razoki; Sari, Nila (Fakultas Kedokteran, Kedokteran Gigi, dan Ilmu Kesehatan, 2024)
Hypertension occurs when a person's blood pressure exceeds the normal limits. This results in increased morbidity and mortality. The method in this study is descriptive, with the use of retrospective research, where the study was conducted by reviewing information or retrieving data that had existed before. Data were collected through polypharmacy prescriptions for patients with high blood pressure at the Royal Prima Medan Hospital between September and November 2023, with 650 prescriptions collected. From the results of this study, the prescriptions that met the inclusion criteria were 100% in accordance with the symptoms, drug doses, mechanisms, procedures, and duration of drug use. A total of 26 prescriptions contained five drugs with 63.41% interaction out of a total of 41 prescriptions. A total of 34 prescriptions contained 6 drugs, with 65.11% of the total 49 prescriptions. A total of 19 prescriptions contained seven drugs, with 82.61% of the total 23 prescriptions. A total of 13 prescriptions containing 8 drugs with a percentage of interactions of 86.67% of the total 15 prescriptions. Most interactions occurred in six prescriptions containing nine drugs, with 100% interaction from a total of six drugs. Most interactions also occurred in four prescriptions containing 10 drugs, with 100% interaction from a total of four drugs.